2017
DOI: 10.1021/acs.orglett.7b03189
|View full text |Cite
|
Sign up to set email alerts
|

Nigegladines A–C, Three Thymoquinone Dimers from Nigella glandulifera

Abstract: Nigegladines A-C (1-3), three thymoquinone dimers, were isolated from the seeds of Nigella glandulifera. Racemic 1 possesses a unique tricyclo[5.4.0.1]dodecane carbon skeleton, and compounds 2 and 3 are two unusual diterpenoid alkaloids with indole cores. Their structures were determined by extensive spectroscopic analyses, and that of 1 was confirmed by single-crystal X-ray diffraction. Both (+)-1 and (-)-1 exhibited significant protective effects against hypoxia/reoxygenation-induced H9c2 myocardial cell inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…This effect was therefore equal to that of the positive control, verapamil (Supporting Information Figure S2). , To elucidate its hypoxia-protective mechanism against H/R-induced cell death, HUVECs were pretreated with 2 and were analyzed for their apoptotic signals through flow cytometry using annexin V–FlTC/PI staining. Compared to the apoptotic percentages of the control group, hypoxia/reoxygenation successfully induced cell apoptosis in the model group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect was therefore equal to that of the positive control, verapamil (Supporting Information Figure S2). , To elucidate its hypoxia-protective mechanism against H/R-induced cell death, HUVECs were pretreated with 2 and were analyzed for their apoptotic signals through flow cytometry using annexin V–FlTC/PI staining. Compared to the apoptotic percentages of the control group, hypoxia/reoxygenation successfully induced cell apoptosis in the model group.…”
Section: Resultsmentioning
confidence: 99%
“…In our ongoing search for new antioxidant and antihypoxic compounds, the endophytic strain Peyronellaea glomerata attracted our attention; a crude extract showed a half-maximal effective concentration (EC 50 ) of 187.5 μM in the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay. Moreover, azaphilone analogues are known to be produced by P. glomerata , which were suggested to be present by UV characteristics during HPLC analysis.…”
mentioning
confidence: 99%
“…Due to its convergency, this reaction exemplifies themes of step and atom economy . Furthermore, the ease of postsynthetic modifications by selective functional group interconversions renders this reaction practical for diversity-oriented synthesis, an increasingly important strategy in drug discovery …”
Section: Discussionmentioning
confidence: 99%
“…Novel dolabellane-type diterpene alkaloids 17-26 were also rare in nature [12][13][14]. In addition, compounds 30-32 with unprecedented skeletons could be speculated to derive from the dimerization of thymoquinone (TQ) [18]. Notably, to date, natural indazole-type alkaloids have only been obtained from species of the genus Nigella and therefore considered as possible taxonomic markers in Nigella genus plants.…”
Section: Alkaloidsmentioning
confidence: 99%
“…e effect was comparable with verapamil, which was known for its protective effect on cardiomyocytes. [18]. A study showed the protective effects of TQ on the cardiac damage in BALB/c mice.…”
Section: Cardiovascular Activity and Vessel Protectionmentioning
confidence: 99%